INVESTIGANDO O CHAT EDUCACIONAL: PODE HAVER COERÊNCIA NO CAOS? - Mazzillo, Tânia Maria da Frota Mattos (Intercâmbio, 2010)
This paper presents a preliminary discussion about the challenges students face to participate in Internet mediated lessons, carried out in public chat room facilities. The structure of participation is analyzed and compared to the classic I-R-E structure, and problems of asymmetry and dominance are dealt with from a quantitative perspective.